East-west corporate networking: A theoretical approach - Katja Gerling (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
In recent years after the beginning of the transition process, firms in Central and Eastern European countries have been trying hard to find access to international markets and production chains. Rapidly changing institutional, technological and demand conditions together with decades of isolation from world markets do not let ,,stand-alone strategies appear very successful in this context. The paper presents networking activities as a promising alternative for Central and Eastern European firms (CEEF) to organize international transactions. As several theories show, network forms of organization can - by establishing an atmosphere of trust and stability and by pooling resources and information - make it possible for network members to realize an economic advantage over external competitors that is higher than in markets or hierarchies. Among various types of networking activities, it is especially long-term-orientated relations that offer the possibility for CEEF to participate in an international exchange of crucial technologies and to upgrade their position in global production chains in the long run.
Keywords: L22; 330; Internationale Unternehmenskooperation; Unternehmensnetzwerk; Theorie der Unternehmung; Technologietransfer; Wettbewerbsstrategie; Osteuropa; Westliche Staaten; Theorie